Mediating roles of institutions in the remittance-growth relationship: Evidence from Nigeria - Ibrahim A. Adekunle; Tolulope O. Williams; Olatunde J. Omokanmi; Serifat O. Onayemi (African Governance and Development Institute (AGDI), 2020)
In this study, we examine the mediating roles of institutions in the remittances growth relationship for some reasons. We found that no country-specific study has towed this line leaving a vacuum in the literature of development and international finance. Most studies along this dimension have been done as a continental panel study with significant attendant deficiencies. Heterogeneous nature of institutional arrangements in African nations makes findings on the moderation roles of institutions in the remittance-growth relationship regional specific. We rely on the autoregressive distributed lag (ARDL) estimation procedure to establish a clear line of thought on the interactions of the variables of interest. Short-run results revealed that remittances inflow positively influence growth, but when institutional factors interact with the remittances variables, only the regulatory quality measures from the product of interactions matters for growth. Nonetheless, long run results revealed that remittances inflow was negatively related with growth, but when interacted with institutional measures and regressed on growth outcomes, we found remittances to positively and statistically influence growth outcomes for all the institutional measures adopted. Therefore, recipient nations should improve on the design and enforcement of laws particularly about their regulatory quality and as well as quality assurance such that they could be positioned to attract increased remittances inflow as well as other sources of external financing needed to augment domestic productivity and growth.
Keywords: E01; E44; F24; 330; Economic Growth; Remittances; Institutions; ARDL; Nigeria